2018
DOI: 10.1155/2018/5484731
|View full text |Cite
|
Sign up to set email alerts
|

Reduced β2GPI Inhibiting Glomerular Mesangial Cells VEGF-NO Axis Uncoupling Induced by High Glucose

Abstract: VEGF-NO axis uncoupling is an important pathogenesis for DN. Reduced β2GPI could play a part in VEGF signaling pathway and has a protective effect on diabetic vascular disease. This study investigates the effect of reduced β2GPI on glomerular mesangial cells VEGF-NO axis uncoupling induced by high glucose. Compared to control group, glomerular mesangial cell line HBZY-1 cells treated with high glucose expressed higher levels of VEGF mRNA and protein and produced more ROS but less NO. The related proteins relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…On the contrary, ECs proliferation in response to VEGF-A can be prevented by using an NO donor ( Nakagawa et al, 2006 ). Furthermore, recent studies have demonstrated that partial reversion of uncoupling of VEGF-A with NO can improve endothelial dysfunction induced by high glucose in type 2 diabetic rats ( Hou et al, 2014 ; Zhou et al, 2018 ). In total, current data suggests that the reduced NO bioavailability in diabetic kidney can further enhance VEGF-A/VEGFR2 signaling and subsequently induce more severely aberrant angiogenesis.…”
Section: The Role Of Vegf-a In Abnormal Angiogenesis Of Dnmentioning
confidence: 99%
“…On the contrary, ECs proliferation in response to VEGF-A can be prevented by using an NO donor ( Nakagawa et al, 2006 ). Furthermore, recent studies have demonstrated that partial reversion of uncoupling of VEGF-A with NO can improve endothelial dysfunction induced by high glucose in type 2 diabetic rats ( Hou et al, 2014 ; Zhou et al, 2018 ). In total, current data suggests that the reduced NO bioavailability in diabetic kidney can further enhance VEGF-A/VEGFR2 signaling and subsequently induce more severely aberrant angiogenesis.…”
Section: The Role Of Vegf-a In Abnormal Angiogenesis Of Dnmentioning
confidence: 99%